Характеризации групп Шункова - Сенашов, В.И. (Український математичний журнал, 2008)
Вивчається будова сім'ї скінченних груп вигляду Lg = ‹a, ag › в періодичній rpyni Шункова. Як наслідок із отриманого результату випливають дві характеризації періодичних груп Шункова. The structure of the family of finite subgroups of the form Lg = ‹a, ag ›
in periodic Shunkov’s group is
studied. As a colorraries of the result obtained, two characterizations of periodic Shunkov’s groups follow.